A Skin-Inspired, Interactive, and Flexible Optoelectronic Device with Hydrated Melanin Nanoparticles in a Protein Hydrogel–Elastomer Hybrid - Gogurla, Narendar; Roy, Biswajit; Min, Kyungtaek; Park, Ji Yong; Kim, Sunghwan (Advanced Materials Technologies, 2020)
Melanin, a biologically occurring pigment featuring broadband optical absorption, ion-binding affinity including antioxidative and radical-scavenging properties, and hydration-dependent electrical conductivity is an ideal natural semiconducting material for interfacing electronics with biological systems. Here, a skin-mimicking optoelectronic device with a melanin nanoparticle (MNP) dispersion in a protein hydrogel–elastomer hybrid (a mimic of epidermis/dermis layers with melanin) and its application as a dopamine sensor and a UV index meter are reported. MNPs dispersed in water are placed in the elastomer reservoir with integrated silver nanowire electrodes and a transparent silk hydrogel window cover; they exhibit n-type semiconducting behavior with increased conductivities compared with those of dehydrated MNPs. Enhanced generation of free radicals by light illumination results in an increase of the electrical conductivity. In addition, the artificial optoelectronic skin interacts with its environment through the silk hydrogel window. Applications of the device, including its use as a dopamine sensor and a UV index meter to detect dopamine and UV light passing through the window, are demonstrated. The sensitivity of the dopamine sensor is enhanced by the light illumination.
Keywords: Artificial skin; Electrical conductivity; Light illumination; Nanowire electrodes; Radical scavenging properties; Semiconducting behavior; Semiconducting materials; Silk proteins; artificial skins; melanin nanoparticles; photoconductivity; sensors; silk proteins